Study Of The Effect Of Sintering Parameters On Characteristics Of W-Bronze Composites Prepared Via Different Densification Techniques - Mohammed, Kahtan S. (2010)

(untitled)
W-bronze composites are very promising MMC material. It has high potential in military and industrial applications and it can replace lead in different fields where the density is of main consideration. In this study, since tungsten metal and bronze alloy are almost completely immiscible in both solid and liquid phases, different approaches and techniques were utilized to attain highly dense and homogenously structured composites. Super-solidus liquid phase sintering with 2 to 3 wt.% Fe additions improved the hardness by two folds and the sintered density by 5 % to 10%. Mechanical alloying of the W, Cu and Sn powder precursors by two-step process yielded composite particles of W impregnated in Cu-Sn matrix. The outcome after sintering was a composite of 85 to 95% of their theoretical density with excellent corrosion and wear resistance properties. By the implementation of a proposed new shell-on-core densification technique, composites of different compositions with 95-99% of their theoretical density were attained. The different W-bronze composite materials produced, were subjected to different laboratory testing and examinations to assess their microstructural, fractural, mechanical, chemical and physical properties.